Pakistan and South-East Asia: Some Personal Recollections - Ibrahim, Ahmad Mohamad (Intellectual Discourse, 2013)
The idea of a separate state for the Muslims of the Indian subcontinent first emerged during the thirties. One of the most prominent persons associated with this idea was Chaudhary Rahmat Ali, who coined the name of Pakistan for such a state. This movement involved not only the students from the Indian sub-continent, but also from other Muslim-majority areas like the then Malaya. This relationship continued with profound social and intellectual benefits for the sub-continent as well as for South-East Asia.